Crocin synergistically enhances the antiproliferative activity of 5‐flurouracil through Wnt/PI3K pathway in a mouse model of colitis‐associated colorectal cancer. Issue 12 (20th August 2018) - Amerizadeh, Forouzan; Rezaei, Nastaran; Rahmani, Farzad; Hassanian, Seyed Mahdi; Moradi‐Marjaneh, Reyhaneh; Fiuji, Hamid; Boroumand, Nadia; Nosrati‐Tirkani, Abolfazl; Ghayour‐Mobarhan, Majid; Ferns, Gordon A.; Khazaei, Majid; Avan, Amir
Abstract: Colorectal cancer (CRC) is the third most common cause of cancer‐related death, and hence there is a need for the identification of novel‐agents to improve the efficacy of existing therapies. There is growing evidence for the antitumor activity of crocin, although its activity and molecular mechanisms in CRC remains to be elucidated. Here we explored the therapeutic application of crocin or its combination with 5‐flurouracil in a mouse model of colitis‐associated colon cancer. The antiproliferative activity of crocin was assessed in two‐dimensional and three‐dimensional cell‐culture models. The migratory behaviors were determined, while the expression levels of several genes were assessed by quantitative reverse transcriptase polymerase chain reaction/Western blot analysis. We examined the anti‐inflammatory properties of crocin by pathological evaluation and disease‐activity index as well as oxidative or antioxidant markers: malondialdehyde (MDA) and total‐thiols (T‐SH) levels and superoxide dismutase (SOD) and catalase (CAT) activity. Crocin suppressed cell‐growth and the invasive behavior of CRC cells through modulation of the Wnt‐pathway and E‐cadherin. Moreover, administration of crocin alone, or in combination with 5‐FU dramatically reduced the tumor number and tumor size in both distal/mid‐colon followed by reduction in disease‐activity index. Crocin also suppressed the colonic inflammation induced by dextran‐sulfate‐sodium and notably recovered the increased levels of MDA, decreased thiol levels and activity of CAT levels. Crocin was able to ameliorate the severe inflammation with mucosal ulcers and high‐grade dysplastic crypts as detected by inflammation score, crypt loss, pathological changes and histology scores. We demonstrated an antitumor activity of crocin in CRC and its potential role in improvement of inflammation with mucosal ulcers and high‐grade dysplastic crypts, supporting the desireability of further investigations on the therapeutic potential of this approach in CRC. Abstract : Schematic representation of the molecular mechanisms involved in the synergistic effects of crocin on 5‐FU. A‐B, Modulation of cyclin D1 and surviving at mRNA levels and PI3K, cyclin D1, P‐Akt and p‐GSK3ɑ/β at protein level in CRC cells after 24 hours exposure to crocin (3 mM) as determined by qRT‐PCR and Western blot analysis. Columns mean values obtained from three independent experiments; bars, SEM. *Significantly different from controls. C, Crocin inhibits PI3K/Akt and Wnt activation and enhances the growth inhibitory effects of 5‐FU through its pronounced antiproliferative and anti‐invasive effects, as well as the attenuation of inflammation and oxidative stress status.